PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKANHASIL BELAJAR MATEMATIKA SISWA KELAS VII.3 SMP NEGERI 9 PEKANBARU - Rischa Endriani; Yenita Roza; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is a classroom action research that aims to improve the learning process and improve students' mathematics learning achievement. The researcher applied the Cooperative Learning Method, Structural approach of classroom Numbered Heads Together at class VII.3 SMP Negeri 9 Pekanbaru, academic year 2015/2016. The Cooperative Learning Method of Numbered Heads Together employs students identification numbers to increase students’ sense of responsibility during the learning process. Data collected during the research was Teacher’s activities data, Students’ activities data and Students’ learning teacher’s achievement as well. The teacher’s and students’ activities data were obtained from observation sheets and students’ observation sheets. While students’ achievement data was obtained from Students’ test result. Then, the data collected were analyzed descriptively. The data analysis of teacher’s and students’ activities showed that the activities of both teacher and students are increasingly appropriate as expected. It is indicated by the teacher doing reflection after the learning process which affects on the teacher’s and students’ performance in the classroom. The improvement of students’ results can be seen from the students’ achievements on KKM. In Cycle 1, students who achieved KKM were 50 % and it increased significantly to 55.5 % in cycle 2. From the result above, the researcher drew a conclusion that there is an improvement on students’ result about 36,1%. after they were given a treatment. It could be stated that using The Cooperative Learning Method of Numbered Heads Together can improve the students’ achievement at class VII.3 SMP Negeri 9 Pekanbaru.KeyWord : Students’ Mathematics Achievement, Cooperative Learning Model Structural Approach of Numbered Heads Together, Classroom Action Research.